2009
DOI: 10.1177/1352458508099611
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of susceptibility loci in benign, aggressive and primary progressive multiple sclerosis in Northern Irish population

Abstract: Objective To investigate the possibility that susceptibility loci in multiple sclerosis (MS) have a role in determining the disease outcome in Northern Ireland population. Background The Genetic Analysis of Multiple Sclerosis in Europeans (GAMES) initiative and follow-up refined analysis identified 15 candidate susceptibility loci within the Northern Irish population for MS. We aimed to investigate the 12 most significant markers for their role in disease outcome. Methods Cases with probable or definite M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Already in 2005, a linkage peak for MS was reported in 19p13 that acted independently from the HLA locus; 24 however, it is not specified as to where on 19p13 this effect was seen. In a paper in 2009, a microsatellite marker on 19p13 was associated to disease outcome, 25 but upon our inspection in a later build of the genome reference, it appears that this marker is more likely to reside at 19q13, an area with several published associations from both linkage and association analysis. 26 , 27 , 28 , 29 Thus, there is weak prior evidence for an importance of this locus in MS.…”
Section: Discussionmentioning
confidence: 84%
“…Already in 2005, a linkage peak for MS was reported in 19p13 that acted independently from the HLA locus; 24 however, it is not specified as to where on 19p13 this effect was seen. In a paper in 2009, a microsatellite marker on 19p13 was associated to disease outcome, 25 but upon our inspection in a later build of the genome reference, it appears that this marker is more likely to reside at 19q13, an area with several published associations from both linkage and association analysis. 26 , 27 , 28 , 29 Thus, there is weak prior evidence for an importance of this locus in MS.…”
Section: Discussionmentioning
confidence: 84%
“…13 The majority of genetic studies have focused on susceptibility variants, and this effort has yielded more than 110 genetic risk factors of MS. 4 In addition, there is evidence that genetic factors may influence disease phenotype such as age at onset, disease severity, and the clinical course. 57 However, 3 genome-wide association studies (GWASs) investigating MS severity have failed to reach a genome-wide significance threshold. 810 A recent meta-analysis of 10 cohorts in 7,125 patients with MS also failed to detect any significant signal.…”
mentioning
confidence: 99%
“…The published results are conflicting. Grey et al suggested a role of TNF-α in the outcome of multiple sclerosis [5]. The results of the association of MS with DRB1*15(2) and TNF-α in the Russian population, reported by Favorova et al indicate the interplay of three loci in susceptibility to multiple sclerosis [3].…”
Section: Introductionmentioning
confidence: 80%